Arsenic Contamination of Water-Soil-Crop System in an Industrial Area of Bangladesh - Ahmed, M.; Kurosawa, K. (International Journal of Environment, 2017)
The arsenic (As) concentrations of irrigation water, soils and vegetables were investigated in an agricultural section of Gazipur industrial area in Bangladesh, where industrial wastewater is mixed with irrigation water. The results showed that the mean As concentration of the irrigation water (0.16-0.62 mg L-1) exceeded the permissible limit for agricultural purposes recommended by the Food and Agriculture Organization (0.10 mg L-1). The mean As concentration of soils (6.48-9.75 mg kg-1) did not exceed the tolerable limit for agricultural soils recommended by the FAO (20.0 mg kg-1). While, the As concentration of the respective vegetables in average varied from 0.63 to 1.07 mg kg-1 dry weight, and the highest As concentration in average was observed in taro root (1.26-2.31 mg kg-1), followed by helencha leaf (1.85-2.02 mg kg-1). The average As concentration of root vegetables (1.84 mg kg-1) exceeded the permissible limit of 1.0 mg kg-1 suggested by the Food and Agriculture Organization, while that of leafy (0.77 mg kg-1) and fruit vegetables (0.14 mg kg-1) did not exceed the limit. Soils irrigated with As containing water that holds much amount of As showed a positive correlation with the vegetable As concentration. A decrease in the As concentration from soil to vegetable was found in root, leafy and fruit vegetables. However, the vegetables were not safe for human consumption. Some countermeasures are, therefore, necessary to reduce the vegetable As concentration. INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-6, Issue-1, Dec-Feb 2016/17, page: 76-86